'Last In–First Out': seasonal variations of non‐structural carbohydrates, glucose‐6‐phosphate and ATP in tubers of two Arum species. (22nd December 2017) - Petrussa, E.; Boscutti, F.; Vianello, A.; Casolo, V.
Abstract: Knowledge on the metabolism of polysaccharide reserves in wild species is still scarce. In natural sites we collected tubers of Arum italicum Mill. and A. maculatum L. – two geophytes with different apparent phenological timing, ecology and chorology – during five stages of the annual cycle in order to understand patterns of reserve accumulation and degradation. Both the entire tuber and its proximal and distal to shoot portion were utilised. Pools of non‐structural carbohydrates (glucose, sucrose and starch), glucose‐6‐phosphate and ATP were analysed as important markers of carbohydrate metabolism. In both species, starch and glucose content of the whole tuber significantly increased from sprouting to the maturation/senescence stages, whereas sucrose showed an opposite trend; ATP and glucose‐6‐phosphate were almost stable and dropped only at the end of the annual cycle. Considering the two different portions of the tuber, both ATP and glucose‐6‐phosphate concentrations were higher in proximity to the shoot in all seasonal stages, except the flowering stage. Our findings suggest that seasonal carbon partitioning in the underground organ is driven by phenology and occurs independently of seasonal climate conditions. Moreover, our results show that starch degradation, sustained by elevated ATP and glucose‐6‐phosphate pools, starts in the peripheral, proximal‐to‐shoot portion of the tuber, consuming starch accumulated in the previous season, as a 'Last In–First Out' mechanism of carbohydrate storage.